Moving LED message by Arduino / Arif Ramlan@Razlan and Muhammad Nur Ikhwan Ramli - Ramlan@Razlan, Arif; Ramli, Muhammad Nur Ikhwan (2015)
In today's world LED-based moving-message displays are becoming popular for transmitting information to large groups of people quickly. These can be used indoors or outdoors. We can find such displays in areas like rail-way platforms, banks, public offices, hotels, training institutes, nightclubs, and shops. Compared to light emitting diodes (LED s), liquid-crystal displays (LCD s) are easy to interface with a micro controller for displaying information as these have many built-in functions. In this project we have used the Arduino ATMEGA328P microcontroller along with a memory. If the user wants to change the message it needs to be done using a computer and hence the person needs to be present at the location of the display board. It means the message cannot be changed from wherever or whenever. Also the display board cannot be placed anywhere because of complex and delicate wiring.